# Calculator search results

Formula
Solve the equation
Graph
$y = \dfrac { 1 } { 2 } x + \dfrac { 1 } { 5 }$
$y = 0.1 \left ( x - 2 \right )$
$x$-intercept
$\left ( - \dfrac { 2 } { 5 } , 0 \right )$
$y$-intercept
$\left ( 0 , \dfrac { 1 } { 5 } \right )$
$x$-intercept
$\left ( 2 , 0 \right )$
$y$-intercept
$\left ( 0 , - \dfrac { 1 } { 5 } \right )$
$\dfrac{ 1 }{ 2 } x+ \dfrac{ 1 }{ 5 } = 0.1 \left( x-2 \right)$
$x = - 1$
 Solve a solution to $x$
$\dfrac { 1 } { 2 } x + \dfrac { 1 } { 5 } = \color{#FF6800}{ 0.1 } \left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right )$
 Multiply each term in parentheses by $0.1$
$\dfrac { 1 } { 2 } x + \dfrac { 1 } { 5 } = \color{#FF6800}{ 0.1 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 0.1 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right )$
$\color{#FF6800}{ \dfrac { 1 } { 2 } } \color{#FF6800}{ x } + \dfrac { 1 } { 5 } = 0.1 x + 0.1 \times \left ( - 2 \right )$
 Calculate the multiplication expression 
$\color{#FF6800}{ \dfrac { x } { 2 } } + \dfrac { 1 } { 5 } = 0.1 x + 0.1 \times \left ( - 2 \right )$
$\dfrac { x } { 2 } + \dfrac { 1 } { 5 } = \color{#FF6800}{ 0.1 } \color{#FF6800}{ x } + 0.1 \times \left ( - 2 \right )$
 Calculate the multiplication expression 
$\dfrac { x } { 2 } + \dfrac { 1 } { 5 } = \color{#FF6800}{ \dfrac { x } { 10 } } + 0.1 \times \left ( - 2 \right )$
$\dfrac { x } { 2 } + \dfrac { 1 } { 5 } = \dfrac { x } { 10 } + \color{#FF6800}{ 0.1 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right )$
 Multiply $0.1$ and $- 2$
$\dfrac { x } { 2 } + \dfrac { 1 } { 5 } = \dfrac { x } { 10 } \color{#FF6800}{ - } \color{#FF6800}{ 0.2 }$
$\dfrac { x } { 2 } + \dfrac { 1 } { 5 } = \dfrac { x } { 10 } \color{#FF6800}{ - } \color{#FF6800}{ 0.2 }$
 Convert decimals to fractions 
$\dfrac { x } { 2 } + \dfrac { 1 } { 5 } = \dfrac { x } { 10 } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 5 } }$
$\color{#FF6800}{ \dfrac { x } { 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 1 } { 5 } } = \color{#FF6800}{ \dfrac { x } { 10 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 5 } }$
 Multiply both sides by the least common multiple for the denominators to eliminate the fraction 
$\color{#FF6800}{ 5 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 2 } = \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
$\color{#FF6800}{ 5 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 2 } = \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
 Organize the expression 
$\color{#FF6800}{ 5 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
$\color{#FF6800}{ 5 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ x } = - 2 - 2$
 Organize the expression 
$\color{#FF6800}{ 4 } \color{#FF6800}{ x } = - 2 - 2$
$4 x = \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
 Find the sum of the negative numbers 
$4 x = \color{#FF6800}{ - } \color{#FF6800}{ 4 }$
$\color{#FF6800}{ 4 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 4 }$
 Divide both sides by the same number 
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 1 }$
 그래프 보기 
Graph
Solution search results